Discretion and public benefit in a regulatory agency : the Australian authorisation process - Nagarajan, Vijaya (Australian National University E Press, 2013)
This book explores the manner in which a variety of public benefits such as environmental protection and consumer safety have been accommodated through the authorisation process within competition law and policy in Australia.